2015
DOI: 10.5414/np300783
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the anaplastic cerebellar liponeurocytoma: case report and review of the literature

Abstract: Cerebellar liponeurocytoma, first recognized as a distinct entity in the revised WHO classification of Tumors of the Central Nervous System in 2000, is a rare tumor with characteristic histological features and predominant location in the cerebellum. The proliferative index is usually low, and previous reports supported a favorable prognosis. We report a case of a second recurrence of a cerebellar liponeurocytoma with increased proliferative and mitotic activity in which extensive immunohistochemical character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The Ki 67/MIB-1 index is usually low (< 5%); however, patients with a relatively high proliferation rate and cytopathologic atypia have been re- ported to have a greater risk of recurrence and, therefore, a poorer prognosis. 2,7,14,20 There is currently no established standard of care, but maximal safe resection followed by postoperative imaging surveillance for recurrence seems prudent. The roles of adjuvant chemotherapy and radiation have not been established.…”
Section: Discussionmentioning
confidence: 99%
“…The Ki 67/MIB-1 index is usually low (< 5%); however, patients with a relatively high proliferation rate and cytopathologic atypia have been re- ported to have a greater risk of recurrence and, therefore, a poorer prognosis. 2,7,14,20 There is currently no established standard of care, but maximal safe resection followed by postoperative imaging surveillance for recurrence seems prudent. The roles of adjuvant chemotherapy and radiation have not been established.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, tumor recurrence was observed in 50% of the patients with cerebellar liponeurocytoma who had not received radiotherapy following tumor surgery, but no tumor recurrence was reported in patients undergoing radiotherapy after surgery [23]. According to various studies, high Ki-67 positive cells (more than 10%) and subtotal tumor resection of the tumor are two main risk factors for tumor recurrence [6,23].…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent in situ hybridization studies of a liponeurocytoma showed no evidence of 1p/19q co-deletion, N-MYC or epidermal growth factor receptor amplification, MYC or EWSR1 rearrangements, or PTEN deletion [ 22 , 23 ]. In contrast to these findings, large cell/anaplastic medulloblastomas are associated with C-MYC or N-MYC amplifications [ 23 ]. Despite this, Wolf et al [ 24 ] and Pikis et al .…”
Section: Discussionmentioning
confidence: 99%
“…Radke et al . were able to show an increase of Ki-67 positive cells in recurrent tumors [ 23 ]. Due to the potentially long-term malignancy, close follow-up is recommended over that period [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%